PENGELOLAAN MANAJEMEN USAHA MELALUI PELATIHAN KEWIRAUSAHAAN (Studi kasus di Pusat Kegiatan Belajar Masyarakat (PKBM ) “KARYA ANAK BANGSA INSTITUTE” Nagori Simanabun Kabupaten Simalungun) - Marto Silalahi; Parlin Dony Sipayung; Sudung Simatupang (Bajang Institute, 2021)
In the development of entrepreneurship, training is needed whose purpose is to make the ability of entrepreneurs to become skilled. The results of the service carried out on entrepreneurship training participants with the aim of being skilled in nailing business management carried out by the PKBM research